Novovznikajúce formy rodinného života na Slovnensku - Tománek, Pavol (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
The present study deals with the family, parenting and the current form of creating families. The work provides insight into the phenomenon of current single, mingle and patchwork families